From unemployment to rapid growth? - Bill Jordan (Intereconomics, 1982)
With unemployment in the OECD countries approaching 30 millions, and with the Mitterrand regime providing yet another example of the failure of demand-led attempts at growth, this article considers the possibility of the advanced industrialised countries returning to a pattern of rapid growth based on plentiful labour supplies. If Keynesian measures to combat high unemployment are rejected, will redundant labour eventually find its own demand, and will this allow a new wave of fast industrial expansion?
Keywords: 330; Industrial Employment